Covid-19: Reflections on threat and uncertainty for the future of elite women's football in England. Issue 1 (4th March 2022) - Clarkson, Beth G.; Culvin, Alex; Pope, Stacey; Parry, Keith D.
ABSTRACT: This commentary offers an analysis of the implications of Covid-19 on the future of elite women's football, with the intention of reflecting on and illuminating the threat and uncertainty facing the game. Topics covered include (1) organisational and economic repercussions; (2) consequences for player contracts, migration and investment; and (3) player wellbeing. These significant challenges require swift and decisive action in order to mitigate their potential effects. Recommendations are made for governing bodies, parent clubs and practitioners, in addition to possible future research directions for academics. We reflect upon what can be done during and post-pandemic to continue the momentum and growth of women's football in England, highlighting the need for football clubs to learn from previous crises by embracing innovation and entrepreneurship.